Apropriação do discurso de inovação curricular em química por professores do ensino médiio - Murilo Cruz Leal (2003)
The aim of this investigation is to analyze how secondary school teachers appropriate the chemistry curricular innovation discourse. The study is based on interviews carried out with 12 teachers who have taken part in the PRÓ-MÉDIO and PRÓ-CIÊNCIAS programs of continued training and innovation implemented in Minas Gerais from 1997 to 1999. The analysis of the teachers discourse is carried out based on, among other references, the complex constitution of the teachers knowledge, involving knowledge of subject matters, curricular knowledge, professional knowledge and experience knowledge such as conceived by Maurice Tardif and collaborators. Taking into account the bibliography on educational change and curricular innovation, this study discusses the conditions of production and proposition of a discourse of curricular innovation based mainly on the economy of linguistic exchange of Pierre Bourdieu. This discussion is carried out in the context constituted by the public policies and educational regulations of the second half of the 90s in Brazil, and by some programs of professional development of teachers in which the discourse of curriculum innovation was presented to secondary school teachers. Finally, the appropriation of the innovation discourse by the teachers is dealt with based on the metalinguistic perspective of Mikhail Bakhtin, using mainly the concepts of appropriation of the discourse of the other and polyphony. Thus, it was possible to listen to the different voices within the discourse of each teacher, in a complex process of justification, accordance, competition and dissimulation, among other dynamics, creating and re-creating meanings of innovation. Each teacher populates the discourse of curriculum innovation with his/her accents and intentions. The teachers experience sometimes acts as an ally to the school culture in the criticism of idealized academic discourses; sometimes it is in opposition to certain traditional teaching practices, becomes an ally of innovation. The high level, the experimental activity, university entrance examinations, school work conditions, the students, their interests and their experiences outside school, and educational policies and programs are some of the elements that mediate the appropriation of the curricular innovation discourse by secondary school teachers.